The Effect Of Peer Feedbacks On Students' Speech - Susie Kusumayanthi; Inti Lestari (Universitas Widyatama, 2022)
In speaking English, students still find many difficulties especially when students make speeches, and unfortunately in giving speeches students are rarely given feedback so they don't know where their mistakes are. Feedback can be given by teachers or their peer. In fact, transactional peer feedback is believed to be able to foster students’ participation as well as communicative competence in compared with the feedback from the teacher (Liu & Carless, 2006). In this paper, the researcher intends to find out how peer feedback is implemented, the focus especially discusses the types of feedback used by the participants in this study, and the effect of conducting peer feedback on students' speech. This study makes use of descriptive qualitative method. Involving 6 participants. The data sources of this research are observations, student speech scores, and interviews. Observations were conducted in 3 weeks, the students' speech scores from the assessments of their peers before and after peer feedback, and interviews. From the observation, the researchers identified the types of feedback that were often used by participants, namely corrective feedback, reinforcing feedback, and didactic feedback. From the interview, the researcher perceived that the students found it beneficial from given feedback. In addition, peer-feedback techniques also have a positive effect on participants. Peer feedback can improve student speech, student confidence, and fun learning activities. Even though it was revealed that peer feedback has a lot of benefits, but most of participants agree that peer feedback activities should be followed by feedback from the teacher. Because they believe the feedback from their teacher is more reliable.